The Implication of Local Wisdom-Based Geographical Curriculum and its Course Book on the Cosmocentric Attitude of the Students in Bali Upland Region - Astawa, Ida Bagus Made (Jurnal Pendidikan dan Pengajaran, 2022)
This article is a publicationÂ  of the results ofÂ  a research aimed at â€œanalyzing the implementation of local wisdomâ€“basedÂ  geographical curriculum supplement (improvement curriculum) andÂ  its courebook on the cosmocentric attitude of the students of SMA inÂ  Bali upland region. This study was designed as a â€œcausal comparative reseaarchâ€ with the sample which was determined purposively in two SMA Negeriâ€™s in the Bali upland region, i.e., SMA Negeri Penebel which represents South Bali and SMA Negeri Busungbiu representing North Bali. The data from teaching were collectedÂ  with obervation sheets andÂ  the data onÂ  the studentsâ€™ cosmocentric attitude with questionnaires (Likert model). The data were thenÂ  analyzed quantitatively using t-test at the 1% level of significance. The results of the study showed that the studentsâ€™ concentric attitude scoresÂ  in Bali upland region increased after the implementation of the local wisdom-based Geography curriculumÂ Â Â Â Â Â Â Â  and the coursebook as the supplement in the teaching of Geography. The increase occurred consistently in all gradesÂ  (GradesÂ  X,XI, and XII) with the mean score of the increaseÂ  at 25.58%. The statistical test showed thatÂ  there is a significant difference in the studentsâ€™ cosmocentric attitudes (the attitudes of Grades X,XI and XII) between before and after the implementation ofÂ  the local wisdom-based geography curriculum and the coursebookÂ  asÂ  the supplementÂ Â  inÂ  teachingÂ  (tobs.Â  Â >Â  tc.v Â ). This shows thatÂ  the local-basedÂ  Geography curriculum supplement and the coursebook have a positive implication to the studentsâ€™ cosmocentric attitude at SMA in Bali upland region.